Five-Tier Diagnostic Test Instrument for Uniform Circular Motion Concepts: Development, Validity, Reliability and Limited Trials - Nisrina Nur Ramadhani; Frida Ulfah Ermawati (Universitas Muhammadiyah Makassar, 2021)
Students' understanding on Physics concepts could be different from each other. Based on the conceptual diagnostic test, especially in five-tier format, the students' different understanding can be categorized into several conception levels. One of them is misconception. For example, students consider that all objects moving on a circular trajectory called uniform circular motion (UCM). According to the Physics concept, an object in UCM must meet three criteria: an object travels along a circular path, the radius of the path is always fixed, and the object moves at a constant speed. However, a standardized conceptual diagnostic test instrument in five-tier format is not yet available. This work aims to develop a five-tier diagnostic test instrument for UCM concepts, perform validity and reliability test and use the developed instrument to identify a number of students’ conception level. The research development method was employed to produce 15 valid and reliable questions. The validity test consisted of internal and external (content and construct empirical) aspects. The internal validity obtained was 88% (very valid). The content aspect, i.e. the false positive=4.95% and the false negative=5.59% both met the criteria 10%. The construct aspect obtained by a Pearson product moment correlation was (5% sig. level). The reliability level of the Alpha Cronbach coefficient shows that the developed instrument was valid and reliable. The limited trial result shows that the students’ conception levels on the UCM concepts was generally lack of knowledge.